Language, Authority, and Digital Media: The Impact on the Legitimacy of Fatwas - Ahmad Suaedy; Fariz Alnizar; Juri Ardiantoro; Said Aqil Siroj (AHKAM : Jurnal Ilmu Syariah, 2023)
This study aims to uncover the position of the Indonesian Ulama Council (Majelis Ulama Indonesia or MUI) in the current institutional context where it has the authority to issue fatwas. The era of disruption and digital revolution poses challenges for MUI. This qualitative study combines content analysis of a text with actor-network analysis of the actors who produce the text. Content analysis of the text was carried out by analyzing the language used in MUI regional fatwas that indicate symptoms of fatwa de-bureaucratization. The next step is to map the discourse arising from the fatwa de-bureaucratization symptoms. This study uses the Discourse Network Analysis (DNA) tool to map the actors involved. This is useful to answer the discourse map and actors involved in producing a discourse. The study results show that MUI faces two main challenges in the digital revolution era. First, the symptom of de-bureaucratization is marked by the increasing number of national issues discussed and decided by MUI regions. Second, depersonalization is characterized by the emergence of celebrity ulama, who often issue fatwas in forums and religious gatherings they possess. Abstrak: Kajian ini berupaya mengungkap posisi Majelis Ulama Indonesia (MUI) saat ini yang secara kelembagaan memiliki kewenangan mengeluarkan fatwa. Era disrupsi dan revolusi digital membawa tantangan tersendiri bagi MUI. Penelitian ini merupakan penelitian kualitatif yang menggabungkan analisis isi dalam sebuah teks dengan analisis jaringan aktor yang memproduksi teks tersebut. Analisis isi teks dilakukan dengan menganalisis data berupa penggunaan bahasa pada fatwa MUI daerah yang menunjukkan gejala debirokratisasi fatwa. Tahap selanjutnya adalah memetakan wacana yang muncul dalam gejala debirokratisasi fatwa. Dalam memetakan aktor-aktor tersebut, penelitian ini menggunakan Discourse Network Analysis (DNA). Hal ini berguna untuk menjawab peta wacana dan aktor yang terlibat dalam memproduksi sebuah wacana. Hasil kajian menunjukkan bahwa ada dua tantangan utama yang dihadapi MUI di era revolusi digital. Pertama, merupakan gejala debirokratisasi yang ditandai dengan semakin banyaknya isu nasional yang dibahas dan diputuskan oleh MUI daerah. Kedua, depersonalisasi ditandai dengan lahirnya ulama selebritas yang kerap mengeluarkan fatwa di forum-forum halakah dan pengajian yang dimiliki.